LEVELS OF SERUM IMMUNOGLOBULINS AND COMPLEMENTS IN PATIENTS WITH VISCERAL LEISHMANIASIS - Wafaa Sadoon Shani (Basrah Journal of Veterinary Research)
Forty sera of patients infected with Leishmania donovani and (10) sera from apparently healthy subject were tested by single radial immunodiffusion to visualize the concentration of IgG, IgM, IgA, C3 and C4. Recent results showed that there was a highly signiﬁcant increase in the level of IgG, IgM, C3 and C4 but there were no signiﬁcant differences in the level of IgA between the two—studied groups.